Exploring the relationship between context and obsessions in individuals with obsessive-compulsive disorder symptoms: a narrative review - Weiss, Franziska; Schwarz, Kristina; Endrass, Tanja (Frontiers in Psychiatry, 2024)
Obsessions in obsessive-compulsive disorder (OCD) have long been proposed to differ from intrusive thoughts in unaffected individuals based on appraisal of the thoughts. However, more recent research indicates that cognitive processes behind obsessions may differ significantly from those in healthy individuals concerning their contextual relationship. This narrative literature review summarizes current evidence for the role of context-relatedness for obsessions in OCD and intrusive thoughts in affected and unaffected individuals. The review encompasses a total of five studies, two of which include individuals diagnosed with OCD (one study also includes a group of unaffected control individuals), while the other three studies investigate the relationship between OCD symptoms and context in unaffected individuals. As assessed by mainly self-reports, the review examines the connection between thoughts and their context, shedding light on how the repetition and automaticity of thoughts, as well as their detachment from context over time contribute to defining obsessions in contrast to intrusive thoughts. However, the link with context depends on the content of the obsessions. We propose the term “decontextualization of thoughts” to describe the phenomenon that obsessions gradually lose their connection with external context during the development of OCD. Future research should investigate whether this hypothesis can be supported by experimental evidence and identify whether this shift might be more likely a cause or a consequence of the disorder.